2013
DOI: 10.1007/s00253-013-5436-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomic and transcriptomic analyses of NaCl-tolerant Staphylococcus sp. OJ82 isolated from fermented seafood

Abstract: Bacteria belonging to the Staphylococcus genus reside in various natural environments; however, only disease-associated Staphylococcus strains have received attention while ecological function and physiologies of non-pathogenic strains were often neglected. Because high level of tolerance against NaCl is a common trait of Staphylococcus, we investigated the characteristics of halotolerance in Staphylococcus sp. OJ82 isolated from fermented seafood containing a high concentration of NaCl. Among the 292 isolates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 53 publications
1
27
0
Order By: Relevance
“…Compared to other bacteria, S. aureus is extremely tolerant to osmotic stress and as shown here can grow on agar plates containing 2 M NaCl. For S. aureus to be able to divide under these conditions, specific osmotic stress adaption processes are activated and as previously reported a large number of transcriptional changes occur (44,45). While intermediate salt concentrations can rescue the growth of a dacA mutant, the strain might not be able to mount the appropriate stress adaption response under extremely high osmolarity conditions, leading to the observed drop in plating efficiency.…”
Section: S Aureus Strains With Altered C-di-amp Levelsmentioning
confidence: 88%
“…Compared to other bacteria, S. aureus is extremely tolerant to osmotic stress and as shown here can grow on agar plates containing 2 M NaCl. For S. aureus to be able to divide under these conditions, specific osmotic stress adaption processes are activated and as previously reported a large number of transcriptional changes occur (44,45). While intermediate salt concentrations can rescue the growth of a dacA mutant, the strain might not be able to mount the appropriate stress adaption response under extremely high osmolarity conditions, leading to the observed drop in plating efficiency.…”
Section: S Aureus Strains With Altered C-di-amp Levelsmentioning
confidence: 88%
“…Choi et al . () performed comparative genomic and transcriptomic analyses regarding Staphylococcus sp. OJ82 tolerant to high concentrations of NaCl isolated from fermented seafood, aiming to understand the physiological responses to high saline concentrations.…”
Section: Molecular Biology Identification Techniques and Their Applicmentioning
confidence: 99%
“…The authors indicated that the metagenomic analysis was, thus, successful in understanding alteration in intestinal microbiota after ingestion of the supplemented diet. Choi et al (2014) performed comparative genomic and transcriptomic analyses regarding Staphylococcus sp. OJ82 tolerant to high concentrations of NaCl isolated from fermented seafood, aiming to understand the physiological responses to high saline concentrations.…”
Section: The New 'Omics' Platform Technologymentioning
confidence: 99%
“…Recent RNA sequencing by way of high-throughput technology has modernized the study of the microbial transcriptome [22][23][24]. Several researchers have studied the differential gene expression of several bacteria in different stressed conditions through transcriptome profiling since RNA-seq analysis has proved the advantages over the disadvantages through hybridization technique and sequence-based technique [25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…is a Gram-positive, mostly non-pathogenic bacteria fitting into the family Staphylococcaceae found worldwide, which is a small constituent of soil microbial flora [32]. The genus Staphylococcus consists of 47 different type species and 24 different subspecies with dependably accessible names [27]. According to Choi and co-workers, resources for isolation of Staphylococcus species comprise of amber [33], insects [34], estuarine and aquatic surface water [35], fermented fish [36], cheese [37], soil, and plant, signifying pervasiveness of the Staphylococcus in the normal environment, while, ecology and physiology of non-pathogenic Staphylococcus in the natural habitat resided ambiguously.…”
Section: Introductionmentioning
confidence: 99%